Comparative Seismic Performance Evaluation of RC Dual System Buildings Under NBC 105:2020 and IS 1893:2016 Across Varying Heights - Pal, Raju; Shrestha, Rojseen; Shrivastav, Mantu (International Journal on Engineering Technology, 2026)
This paper presents a comparative seismic performance evaluation of reinforced concrete (RC) dual system buildings, comprising shear walls and moment-resisting frames, of varying heights (4, 8, and 16 storeys) analyzed under NBC 105:2020 and IS 1893 (Part I):2016. Key seismic performance indices base shear, lateral storey displacement, inter-storey drift, and fundamental time period are systematically compared using the Response Spectrum Method. NBC 105:2020 yields significantly higher seismic demands, with base shear ratios of approximately 1.6, 3.0, and 5.2 times that of IS 1893:2016 for 4-, 8-, and 16-storey buildings, respectively. These differences arise from NBC 105:2020’s probabilistic seismic hazard framework, higher spectral accelerations, and the combined application of ductility and overstrength factors in place of a single response reduction factor. The study highlights the conservative nature of NBC 105:2020 and its implications for structural design economy and safety in seismically active regions like Nepal.